Photodynamic therapy with a cationic functionalized fullerene rescues mice from fatal wound infections. (December 2010) - Lu, Zongshun; Dai, Tianhong; Huang, Liyi; Kurup, Divya B; Tegos, George P; Jahnke, Ashlee; Wharton, Tim; Hamblin, Michael R
Aims: Fullerenes are under intensive study for potential biomedical applications. We have previously reported that a C60 fullerene functionalized with three dimethylpyrrolidinium groups (BF6) is a highly active broad-spectrum antimicrobial photosensitizer in vitro when combined with white-light illumination. We asked whether this high degree of in vitro activity would translate into an in vivo therapeutic effect in two potentially lethal mouse models of infected wounds.Materials & methods: We used stable bioluminescent bacteria and a low light imaging system to follow the progress of the infection noninvasively in real time. An excisional wound on the mouse back was contaminated with one of two bioluminescent Gram-negative species, Proteus mirabilis (2.5 × 10 7 cells) and Pseudomonas aeruginosa (5 × 10 6 cells). A solution of BF6 was placed into the wound followed by delivery of up to 180 J/cm 2 of broadband white light (400–700 nm).Results: In both cases there was a light-dose-dependent reduction of bioluminescence from the wound not observed in control groups (light alone or BF6 alone). Fullerene-mediated photodynamic therapy of mice infected with P. mirabilis led to 82% survival compared with 8% survival without treatment (p < 0.001). Photodynamic therapy of mice infected with highly virulent P. aeruginosa did not lead to survival, but when photodynamic therapy was combined with a suboptimal dose of the antibiotic tobramycin (6 mg/kg for 1 day) there was a synergistic therapeutic effect with a survival of 60% compared with a survival of 20% with tobramycin alone (p < 0.01).Conclusion: These data suggest that cationic fullerenes have clinical potential as an antimicrobial photosensitizer for superficial infections where red light is not needed to penetrate tissue.